Still the Exception?: Challenging Ideas of Gender in Norwegian Policing - Jon, Nina (The British journal of criminology, 2022)
This article is an empirical exploration of the role of gender in today’s Norwegian police force. For this study, 21 emergency response officers were interviewed as part of an investigation into the role played by gender in operational police work. This study indicates that changes towards a more gender-equal Norwegian society, combined with general developments within the police at a time when the number of women in the police force has increased considerably, have led to female operational police officers finding that their gender is not a problem. The findings challenge earlier models of theorising and conceptualisation, and point to the need to avoid perpetuating notions that may needlessly limit policewomen’s individual freedom and agency on account of their gender.